Idee liberalne w polskiej myśli ekonomicznej po II wojnie światowej do lat 70. XX wieku - Walasek, Mateusz (Gospodarka w Praktyce i Teorii, 2012)
The essay shows how in the era of central planning ideology, Polish economists expressed the conviction of the need to respect certain ideas of liberal economics. In the first part we present ideas of Adam Krzyżanowski and Edward Taylor - writers who were active before the war and were able to continue their work in early post-war period. In the next part it has been shown views of authors taking part in discussion about Central Board of Planning and in discussion about the law of value. Czesław Bobrowski, Włodzimierz Brus, Jan Mujżel, Józef Popkiewicz, Stefan Kurowski postulated implementation of market mechanism to planed economy, but in practice never propagated abandon of central planning nor privatization of production resources.